Exploring Turkish women’s gynecological examination perceptions based on their metaphors: a qualitative study - Seval Cambaz Ulaş; Selda İldan Çalim; Aynur Çetinkaya (BMC Women's Health)
Abstract Background During the gynecological examination, women especially feel uncomfortable with the lithotomy position and experience shame and anxiety. This study aims to explore metaphors used by women who have experienced gynecological examinations. Methods This study is qualitative and phenomenological. The study group consisted of 90 women. Data were collected online using a data form in May-June 2021. It consisted of the sociodemographic characteristics of women and their metaphorical perceptions of gynecological examination. Data were analyzed and interpreted using a metaphorical analytical method inspired by Kochis and Gillespie. Metaphoric linguistic expressions, sequences, words, and sentences related to each other, were highlighted. The Consolidated criteria for Reporting Qualitative research (COREQ) checklist was used in the study report. Results The average age of the women was 37.29 ± 10.14, and 73.0% were high school graduates. Three different conceptual categories were created by associating each metaphor image with a certain theme concerning women’s perspective on gynecological examination. The characteristics compiled during the category development phase were used to collect 24 metaphors under a specific category. The metaphor revealed that the process, instrument (examination table), and affective aspects of the gynecological examination are in interaction. In this study was found that the main metaphor image for the gynecological table was a “fork,” the gynecological examination brought to mind “the pregnancy” because of the reason for the procedure, and most of the women used the metaphors of “ache/pain” for their gynecological examination experience. Conclusions The metaphors used for the gynecological examination expressions suggested that women’s experiences were negative. Such metaphors may reflect physical and emotional discomfort experienced during the examination. Health professionals’ understanding of these negative perceptions and their empathy may facilitate positive experiences for women and the detection and treatment of health problems.